2009
DOI: 10.1007/s11205-009-9449-2
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Life and Perceptions of Crime in Saskatoon, Canada

Abstract: Quality of life, Perceptions of crime, neighbourhood, Social cohesion,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
22
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 20 publications
0
22
0
1
Order By: Relevance
“…The link itself is fairly well-established: several studies have found that affective measures of fear of crime are associated with poorer mental and physical health, although effect sizes are generally modest (Beatty et al, 2005;Chandola, 2001;Green et al, 2002;Roberts et al, 2010;Ross, 1993;Ross and Mirowsky, 2001;Stafford et al, 2007). There is also some evidence of an association between cognitive measures (perceived crime or risk of crime) and poorer health outcomes (Kitchen and Williams, 2010;White et al, 1987), although the findings here are less consistent, and other studies find no association (Bowling et al, 2006;Johnson et al, 2009).…”
Section: Fear Of Crime and Health And Wellbeingmentioning
confidence: 99%
“…The link itself is fairly well-established: several studies have found that affective measures of fear of crime are associated with poorer mental and physical health, although effect sizes are generally modest (Beatty et al, 2005;Chandola, 2001;Green et al, 2002;Roberts et al, 2010;Ross, 1993;Ross and Mirowsky, 2001;Stafford et al, 2007). There is also some evidence of an association between cognitive measures (perceived crime or risk of crime) and poorer health outcomes (Kitchen and Williams, 2010;White et al, 1987), although the findings here are less consistent, and other studies find no association (Bowling et al, 2006;Johnson et al, 2009).…”
Section: Fear Of Crime and Health And Wellbeingmentioning
confidence: 99%
“…Like a significant amount of inner city neighbourhoods in cities across Canada and North America, neighbourhoods with lowest QOL scores are among the oldest areas of Saskatoon are the core areas where poverty flourishes. There is a disparity between these neighbourhoods and other parties of the city when it comes to things such as health and crime [109,110]. Neighbourhoods with high QOL scores clustered on the east side of the city further highlight this disparity.…”
Section: A Preliminary Case Study Of the Proposed Modelmentioning
confidence: 99%
“…,Moore (2006),Cohen (2008),Kitchen and Williams (2010),Braakmann (2012),Ambrey et al (2014),Dustmann and Fasani (2016) andJanke et al (2016).…”
mentioning
confidence: 99%